The strangest man : the hidden life of Paul Dirac, quantam genius - Farmelo, Graham (Faber and Faber Ltd, 2009)
From the Publisher: Paul Dirac was among the great scientific geniuses of the modern age. One of the discoverers of quantum mechanics, the most revolutionary theory of the past century, his contributions had a unique insight, eloquence, clarity, and mathematical power. His prediction of antimatter was one of the greatest triumphs in the history of physics. One of Einstein's most admired colleagues, Dirac was in 1933 the youngest theoretician ever to win the Nobel Prize in physics. Dirac's personality is legendary. He was an extraordinarily reserved loner, relentlessly literal-minded and appeared to have no empathy with most people. Yet he was a family man and was intensely loyal to his friends. His tastes in the arts ranged from Beethoven to Cher, from Rembrandt to Mickey Mouse. Based on previously undiscovered archives, The Strangest Man reveals the many facets of Dirac's brilliantly original mind. A compelling human story, The Strangest Man also depicts a spectacularly exciting era in scientific history.